Legitimacy of Account Blocking by Third Parties in the Human Rights Paradigm - Khofidhotur Rovida; Izzah Khalif Raihan Abidin; Hervina Puspitasari (Universitas Sriwijaya, 2026)
Account blocking by third parties, such as the Financial Transaction Reports and Analysis Centre (PPATK), is a crucial issue within the human rights (HAM) paradigm because it restricts individual ownership rights and economic freedom. This study aims to analyse the legitimacy of account blocking without a court decision and to examine PPATK's legal standing among customers, banks, and law enforcement officials. Using a normative juridical method with a statutory and conceptual approach, this study finds that the PPATK does not have attributive authority to block accounts directly but rather has the authority to request a